Estatuto da forma cê: clítico ou palavra? - Liliane Pereira Barbosa (2005)
The fact that the Portuguese pronoun cê can be considered a syntactic pronominal clitic in previous investigations and the verification that this form is possible to appear in positions in which the clitic does not appear leads us to question its true character. Basing on the Clitization Theory and through their phonological, morphological and syntactic tests proposed to identify clitics, it is verified that cê behaves not as a clitic but as full word. This verification is ratified according to the theoretic framework of the Prosodic Phonology. With support on the Prosodic Phonology it is proposed the lack of tonicity perceived in the cê pronoun lays in the level of the phrase, not in the word. This lack of tonicity is justified by the possibility of alternation of the accentual prominence in the prosodic constituent intonational phrase. Since this constituent is related to semantic, syntactic and performance of the speaker aspects, it determines the strong and the weak node to cê, that is, its strong or weak position in the sentence.